Administration of Warfarin Inhibits the Development of Cerulein-Induced Edematous Acute Pancreatitis in Rats - Katarzyna Konarska-Bajda; Piotr Ceranowicz; Jakub Cieszkowski; Grzegorz Ginter; Agnieszka Stempniewicz; Krystyna Gałązka; Beata Kuśnierz-Cabala; Paulina Dumnicka; Joanna Bonior; Zygmunt Warzecha (Biomolecules, 2023)
Acute pancreatitis (AP) is a severe disease with high morbidity and mortality in which inflammation and coagulation play crucial roles. The development of inflammation leads to vascular injury, endothelium and leukocytes stimulation, and an increased level of tissue factor, which results in the activation of the coagulation process. For this reason, anticoagulants may be considered as a therapeutic option in AP. Previous studies have shown that pretreatment with heparin, low-molecular-weight heparin (LMWH), or acenocoumarol inhibits the development of AP. The aim of the present study was to check if pretreatment with warfarin affects the development of edematous pancreatitis evoked by cerulein. Warfarin (90, 180, or 270 µg/kg/dose) or saline were administered intragastrically once a day for 7 days consecutively before the induction of AP. AP was evoked by the intraperitoneal administration of cerulein. The pre-administration of warfarin at doses of 90 or 180 µg/kg/dose reduced the histological signs of pancreatic damage in animals with the induction of AP. Additionally, other parameters of AP, such as an increase in the serum activity of lipase and amylase, the plasma concentration of D-dimer, and interleukin-1β, were decreased. In addition, pretreatment with warfarin administered at doses of 90 or 180 µg/kg/dose reversed the limitation of pancreatic blood flow evoked by AP development. Warfarin administered at a dose of 270 µg/kg/dose did not exhibit a preventive effect in cerulein-induced AP. Conclusion: Pretreatment with low doses of warfarin inhibits the development of AP evoked by the intraperitoneal administration of cerulein.